Prevalence of Gulf war veterans who believe they have Gulf war syndrome: questionnaire study. Issue 7311 (1st September 2001) - Chalder, T; Hotopf, M; Unwin, C; Hull, L; Ismail, K; David, A; Wessely, S
Abstract: Objectives: To determine how many veterans in a random sample of British veterans who served in the Gulf war believe they have "Gulf war syndrome, " to examine factors associated with the presence of this belief, and to compare the health status of those who believe they have Gulf war syndrome with those who do not. Design: Questionnaire study asking British Gulf war veterans whether they believe they have Gulf war syndrome and about symptoms, fatigue, psychological distress, post-traumatic stress, physical functioning, and their perception of health. Participants: 2961 respondents to questionnaires sent out to a random sample of 4250 Gulf war veterans (69.7%). Main outcome measure: The proportion of veterans who believe they have Gulf war syndrome. Results: Overall, 17.3% (95% confidence interval 15.9 to 18.7) of the respondents believed they had Gulf war syndrome. The belief was associated with the veteran having poor health, not serving in the army when responding to the questionnaire, and having received a high number of vaccinations before deployment to the Gulf. The strongest association was knowing another person who also thought they had Gulf war syndrome. Conclusions: Substantial numbers of British Gulf war veterans believe they have Gulf war syndrome, which is associated with psychological distress, a high number of symptoms, and some reduction in activity levels. A combination of biological, psychological, and sociological factors are associated with the belief, and these factors should be addressed in clinical practice.